2020
DOI: 10.1152/ajpheart.00379.2020
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm dynamics of the aging heart: an experimental study using conscious, restrained mice

Abstract: Heart rate variability (HRV) is a measure of variation in time interval between heartbeats and reflects the influence of autonomic nervous system and circulating/locally released factors on sinoatrial node discharge. Here, we tested whether electrocardiograms (ECGs) obtained in conscious, restrained mice, a condition that affects sympathovagal balance, reveal alterations of heart rhythm dynamics with aging. Moreover, based on emergence of sodium channels as modulators of pacemaker activity, we addressed conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…A reduction in the parasympathetic tone occurs with age and it has been suggested to compensate for the pacemaker intrinsic slowdown [61,62]. Heart rate variability, which is largely accepted to reflect the parasympathetic modulation of the heart, decreases by more than 60% from 20-year-old to 60-year-old subjects [63][64][65], suggesting a loss of parasympathetic tone with age. Interestingly, a biological model has been proposed to explain the decrease in heart rate variability.…”
Section: Pacemaker's Parasympathetic Decelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in the parasympathetic tone occurs with age and it has been suggested to compensate for the pacemaker intrinsic slowdown [61,62]. Heart rate variability, which is largely accepted to reflect the parasympathetic modulation of the heart, decreases by more than 60% from 20-year-old to 60-year-old subjects [63][64][65], suggesting a loss of parasympathetic tone with age. Interestingly, a biological model has been proposed to explain the decrease in heart rate variability.…”
Section: Pacemaker's Parasympathetic Decelerationmentioning
confidence: 99%
“…A reduced responsivity to the parasympathetic drive can also be attributable to a common mechanism such as a reduction of cAMP/PKA sensitivity [ 99 ] or an age-reduced sensitivity to phosphodiesterase inhibition [ 96 ]. Parasympathetic input then appears to be attenuated in old animals, generating an abnormal sympathovagal balance with age [ 65 ].…”
Section: Aging and Pacemaker Acceleration And Deceleration At The Mol...mentioning
confidence: 99%
“…Data showed that a bunch of genes displayed different m 6 A methylation levels and differently expressed mRNA levels (Table 4 ). Most of these hyper- or hypo- methylated and differently expressed genes were reported to have a role in aging of human and other mammalian species, such as NAV1, FOXO6, CARD6, FAHD1, TCF4, DNMBP, and HMGCS 1 [ 46 52 ]. Some of the genes were confirmed to be enrolled in the process of ovarian tumorgenesis, such as FBXO16, TTYH3, VSIG4, ZC3H13, NCK1, BMI1, USP1, DYRK2, DNAJB6, TNC, KLF12, LATS2, and FOXP1 [ 53 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…plus propranolol (1 mg/kg body weight, i.p.) for combined block of sympathetic and parasympathetic branches of the autonomic nervous system (combined autonomic block) ( 24 , 28 ). Drugs were dissolved in USP saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of heart rate and heart rate variability (HRV) was conducted on electrocardiographic recordings using LabChart 8 (ADinstruments) and the HRV module, as reported previously ( 24 ). Lead I was used to obtain HRV parameters and other leads were employed as alternative source of analysis and/or for validation of obtained results.…”
Section: Methodsmentioning
confidence: 99%